Fontes de lipídios na alimentação de frangos de corte - Potença, Alexandra (2008)
Two experiments were carried out to evaluate the performance, abdominal fat, bone parameters, fatty acids profile and meat quality parameters of broiler chicken's meat fed with different fatty sources. In the experiment one, a completely randomized design was used with four treatments, eight replicates and 49 birds per experimental unit where the birds received diets with different fatty sources: soybean oil (SO), cottonseed oil (CO), poultry offal (PO) and beef tallow (BT), during the initial phase (1 to 21 days). In the growing phase (22 to 42 days) each treatment used in the initial phase was divided in two treatments and one group of birds continuous receiving the same source of oil used before and the other group received SO in the diet. In this phase there were seven treatments and four replicates. It was include 3% and 4.5% of oil in the initial and in the growing phase respectively. In both phases there was no effect (P>0.05) of fatty sources on the birds performance, abdominal fat and bone parameters. There was difference (P<0.05) between treatments for fatty acid profile of the thigh meat. In the experiment two, during initial phase the birds received the same diet with soybean oil as fatty source at 3%. In the growing phase a completely randomized designed was adopted with five treatments, six replicates and 30 birds per experimental unit. The birds received diets with different sources of fatty: SO, rapeseed (RO), sunflower oil (SO), PO and BT. There was no effect (P>0.05) of the treatments in the birds performance, abdominal fat and meat and bone quality parameters. There was difference (P<0.05) between treatments in the fatty acid profile of the meat. The results suggests that the enrichment of the diets with different sources of oil, rich in polyunsaturated fatty acids, promotes modifications at lipid composition in thigh's meat of the broiler chicken.